2014
DOI: 10.1002/2014jd022353
|View full text |Cite
|
Sign up to set email alerts
|

First observations of polarized scattering over ice clouds at close‐to‐millimeter wavelengths (157 GHz) with MADRAS on board the Megha‐Tropiques mission

Abstract: Polarized scattering by frozen hydrometeors is investigated for the first time up to 157 GHz, based on the passive microwave observations of the Microwave Analysis and Detection of Rain and Atmospheric Structures (MADRAS) instrument on board the Indo-French Megha-Tropiques satellite mission. A comparison with time-coincident Tropical Rainfall Measurement Mission Microwave Imager records confirms the consistency of the coincident observations collected independently by the two instruments up to 89 GHz. The MADR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 40 publications
17
55
0
Order By: Relevance
“…Compared with 166 GHz, the 89 GHz TB V has a narrower dynamic range (∼ 60 K) before reaching the PD peak for both oceanic and land conditions. This result is consistent with the TMI 85 GHz PD behavior reported by Prigent et al (2005), but Defer et al (2014) reported a somewhat smaller PD peak amplitude (∼ 8 K) at 89 GHz using the MADRAS instrument onboard the Indo-French MeghaTropiques satellite mission. At 166 GHz, PD does not reach its peak until about 80 K colder than the clear-sky radiance.…”
Section: Pd-tbv Relationship Observed By Gmi and Cossirsupporting
confidence: 82%
See 3 more Smart Citations
“…Compared with 166 GHz, the 89 GHz TB V has a narrower dynamic range (∼ 60 K) before reaching the PD peak for both oceanic and land conditions. This result is consistent with the TMI 85 GHz PD behavior reported by Prigent et al (2005), but Defer et al (2014) reported a somewhat smaller PD peak amplitude (∼ 8 K) at 89 GHz using the MADRAS instrument onboard the Indo-French MeghaTropiques satellite mission. At 166 GHz, PD does not reach its peak until about 80 K colder than the clear-sky radiance.…”
Section: Pd-tbv Relationship Observed By Gmi and Cossirsupporting
confidence: 82%
“…This finding is consistent with Defer et al (2014) using MADRAS's 157 GHz polarization channel pairs. The PD bell curve gradually diminishes at clear-sky scenes (TB V ∼ 280 K), but approaches ∼ +2 K at very thick convective clouds (TB V ∼ 100 K).…”
Section: Pd-tbv Relationship Observed By Gmi and Cossirsupporting
confidence: 81%
See 2 more Smart Citations
“…Recently, the polarimetric data have been used to study ice microphysical properties (e.g., Hioki et al, 2016;Homeyer & Kumjian, 2015;Skofronick-Jackson et al, 2015). In particular, studies of PD from passive and active spaceborne measurements at visible and microwave wavelengths show that nonspherical ice crystals are not randomly oriented but usually horizontally oriented (Davis et al, 2005(Davis et al, , 2007Defer et al, 2014;Prigent et al, 2001Prigent et al, , 2005Zhou et al, 2012). Gong and Wu (2017) (GW17 hereafter) first identified the similar features from the GPM-GMI 166 and 89 GHz observations.…”
Section: Supporting Informationmentioning
confidence: 99%